On Some Numerical Radius Inequalities Involving Generalized Aluthge Transform - Javariya Hyder; Muhammad Saeed Akram; Abdulaziz S. Alofi; Dilruba Akter (Journal of Function Spaces)
Let S be any bounded linear operator defined on a complex Hilbert space H. In this paper, we present some numerical radius inequalities involving the generalized Aluthge transform to attain upper bounds for numerical radius. Numerical computations are carried out for some particular cases of generalized Aluthge transform.